The Struggle is Beautiful: On the Aesthetics of Leftist Politics - Hartle, Johan (The Nordic Journal of Aesthetics, 2014)
Aesthetic discourse has always openly or secretly been linked to political projects. According to some main strands of aesthetic discourse modern aesthetics mirrors the structure of social and political emancipation and key elements of aesthetic discourse coincide with the political ontology of the left. Marxist and Post-Marxist critics have emphasized that the struggle for emancipation is indirectly present in the historical constitution of aesthetics as a discipline – although in a merely imaginary and displaced form. Therefore, however, it is also partly of the same structure as what is normally described as “aesthetic”. Against this background aesthetic attributes (‘beauty’) can be ascribed to forms of emancipatory politics as well.